Accounting for the Physical and Mental Health Benefits of Entry Into Marriage: A Genetically Informed Study of Selection and Causation - Horn, Erin E. (2012)
Married adults show better psychological adjustment and physical health than their separated/divorced or never-married counterparts. However, this apparent “marriage benefit” may be due to social selection, social causation, or both processes. Genetically informed research designs offer critical advantages for helping to disentangle selection from causation by controlling for measured and unmeasured genetic and shared environmental selection. Using young-adult twin and sibling pairs from the National Longitudinal Study of Adolescent Health (Harris, 2009), we conducted genetically informed analyses of the association between entry into marriage, cohabitation, or singlehood and multiple indices of psychological and physical health. The relation between physical health and marriage was completely explained by nonrandom selection. For internalizing behaviors, selection did not fully explain the benefits of marriage or cohabitation relative to being single, whereas for externalizing symptoms, marriage predicted benefits over cohabitation. The genetically informed approach provides perhaps the strongest nonexperimental evidence that these observed effects are causal.